The Phenomenon of Julid Fi Sabilillah on Instagram as a Form of Rejection of Israel's Genocide against Palestine: A Critical Discourse Analysis - Khoerunisa, Syahda Fadliani; Ulfah, Nadia Maelani; Yanti, Windy; Ridha, Ridha; Lukman, Fahmy (Islamic Research, 2025)
Julid Fi Sabilillah emerged as a response to the massive genocide by Israel that began on October 7, 2023. This research aims to unveil the phenomenon of Julid Fi Sabilillah on Instagram using a critical discourse analysis approach and to explain its role and influence regarding the genocide committed by Israel against Palestine. The methodology employed in this study is qualitative, utilizing Norman Fairclough's critical discourse analysis model. The findings indicate that the phenomenon of Julid Fi Sabilillah on Instagram represents an effort by pro-Palestinian Indonesian citizens to resist Israel, triggered by the genocide that started on October 7, 2023. This is manifested through comments and posts laden with protests against Israel and calls for public participation. Julid Fi Sabilillah plays a role in undermining the morale of IDF (Israel Defense Forces) soldiers and countering their propaganda on social media, causing stress and disruption that leads them to lock and limit their Instagram accounts.